2023
DOI: 10.1029/2022ef003057
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Rising CO2 Amplify the Impact of Land Use/Cover Change on Carbon Budget Differentially Across China

Abstract: Optimizing land use/cover (LUC) decisions has been deemed the most efficient and low-cost way to mitigate climate change and realize carbon neutrality (Drever et al., 2021;Fargione Joseph et al., 2018;Griscom Bronson et al., 2017). Meanwhile, numerous studies have asserted that climate change and rising CO 2 (CCRC) have a considerable effect on vegetation growth and decomposition (Mitchard, 2018;Walker et al., 2021). These global change factors undoubtedly interact with land use/cover change (LUCC) and affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 111 publications
1
4
0
Order By: Relevance
“…This truth also told us that the impact of different ERPs actions on different ecosystem services is varied, and this difference varies with differences in climate background. This finding was also proven in prior studies (Griscom Bronson et al, 2017;Huang et al, 2023). In addition, we should note that the per unit area sandstorm prevention improvement contributed by ERPs in areas with >500 mm precipitation was lower than that in areas with 400-500 mm precipitation (Figure 4d).…”
Section: Re Sultssupporting
confidence: 87%
See 2 more Smart Citations
“…This truth also told us that the impact of different ERPs actions on different ecosystem services is varied, and this difference varies with differences in climate background. This finding was also proven in prior studies (Griscom Bronson et al, 2017;Huang et al, 2023). In addition, we should note that the per unit area sandstorm prevention improvement contributed by ERPs in areas with >500 mm precipitation was lower than that in areas with 400-500 mm precipitation (Figure 4d).…”
Section: Re Sultssupporting
confidence: 87%
“…To quantify the effect of ERPs on ecosystem services change through the BBMS, we constructed a mechanism by summing the area fraction change of LUCs in each 10 × 10 km 2 grid cell (Figure S4) (Equation 1) with reference to our prior study (Huang et al, 2023). For more details, please refer to Text S4 in Supporting Information.ESigoodbreak=fnormalF,igoodbreak×ESF,igoodbreak+fC,igoodbreak×ESnormalC,igoodbreak+goodbreak+fnormalG,igoodbreak×ESnormalG,iwhere ESi denotes the ecosystem services (including carbon sequestration, water retention, soil retention, and sandstorm prevention) in grid cell i ; fnormalF,i, fnormalC,i, and fnormalG,i denote the area fractions of forest, cropland, and grassland in grid cell i , respectively; and ESnormalF,i, ESnormalC,i, and ESnormalG,i denote the ecosystem services per unit area of forest, cropland, and grassland in grid cell i , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Satellite data have shown that ecological restoration projects play a significant role in increasing global vegetation cover, particularly through afforestation efforts in forests and croplands (Chen et al, 2019; Piao et al, 2020). Such restoration projects can increase regional carbon stocks, mitigate climate change and global warming, and prevent soil erosion (Huang et al, 2023; Liu et al, 2023). However, they also have some potential risks, including a significant reduction in runoff owing to plant interception and an increased risk of drought resulting from increased evapotranspiration from afforestation (Ma et al, 2023; Zhou et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Due to increasing urbanization, rapid development of transportation industry and intensification of industrial pollution, in the context of environmental stress, the irrational distribution of spatial and non-spatial structures of forest stands has caused competition for spatial ecological niches within the main species of P. koraiensis Nakai in plantation forests in northeastern China (Huang et al, 2023), resulting in unhealthy stands and unstable structural characteristics. Leaf pigment content, recognized as an important metric for assessing plant and forest health, has been identified as a trait intrinsically linked to ecosystem structure and relationships within its biodiversity (Miraglio et al, 2019).…”
Section: Introductionmentioning
confidence: 99%